The management of linguistic and cultural minorities in a national state - Bussotti, L. (2017)
This short reflection aims to present how Italy has managed the linguistic and cultural differences inside its national territories, considering three fundamental historical steps: the first period of unification; the Fascism; the period after the end of the Second World War, culminating in the approval of the first organic law that protects its historical linguistic minorities.